(untitled) (Journal of the Bangladesh Agricultural University, 2025)
The research was conducted to evaluate the potential of ensiling caged layer droppings (CLD) with roadside green grass (RGG) and rice straw (RS) (Oryza sativa L.) in different amounts to assess the nutritional value of ensilage as well as preservation quality. Four different treatments T0 (0% CLD+ 45% RGG + 50% RS +5% molasses), T1 (10% CLD+ 35% RGG + 50% RS +5% molasses), T2 (20% CLD+ 25% RGG + 50% RS +5% molasses) and T3 (30% CLD+ 15% RGG + 50% RS +5% molasses) were prepared to evaluate the organoleptic quality (color, smell, texture, fungal growth), pH, nutritional composition (dry matter, crude protein, crude fiber, ether-extract, ash), in vitro organic matter digestibility (IVOMD) and metabolizable energy (ME) at 0th, 7th, 14th, 21st, 28th days of ensiling. All parameters of different treatments changed significantly (p<0.05) under different ensiling periods. Organoleptic parameters (color, smell, texture, fungal growth) were satisfactory regarding increased CLD and ensiling period. pH was significantly (p<0.05) dropped under 5 after 28 days of ensiling. Among all treatments, T3 (30%) had significantly (p<0.05) the highest crude protein (13.10%) but significantly (p<0.05) the lowest DM (57.47%), CF (16.33%), EE (1.91%) respectively. After 28 days of ensiling only CP significantly (p<0.05) increased from 11.58% to 13.11% but DM, CF, EE and Ash decreased significantly (p<0.05). In vitro organic matter digestibility and Metabolizable Energy content significantly (p<0.05) increased in T3 after 28 days of ensiling. Considering all the physical and chemical parameters, T3 will be the potential source of cattle feed. However, feeding trials are needed to justify the present findings. J Bangladesh Agril Univ 23(2): 175-183, 2025